2004
DOI: 10.1016/j.jpainsymman.2004.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Predicting aberrant drug behavior in patients treated for chronic pain: importance of abuse history

Abstract: Physicians can encounter problems in prescribing opioids for some patients with chronic pain such as multiple unsanctioned dose escalations, episodes of lost or stolen prescriptions, and positive urine drug screenings for illicit substances. This study explored the usefulness of questions on abuse history in predicting problems with prescribing opioids for patients at a hospital-based pain management program. One hundred forty-five (145) patients who were taking long- and short-acting opioids for their pain we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
228
4
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 337 publications
(243 citation statements)
references
References 16 publications
10
228
4
1
Order By: Relevance
“…The present findings agree with previous work among non-HIV patients in which prior substance abuse emerged as one of the strongest risk factors for opiate misuse (Schofferman 1993;Dunbar and Katz 1996;Michna et al 2004). Schieffer et al (2005) in the largest study to date reported that chronic pain patients with a history of substance abuse evidenced higher rates of medication misuse compared to those without such history despite equivalent levels of prescribed opiates and similar self-ratings of medication effectiveness.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present findings agree with previous work among non-HIV patients in which prior substance abuse emerged as one of the strongest risk factors for opiate misuse (Schofferman 1993;Dunbar and Katz 1996;Michna et al 2004). Schieffer et al (2005) in the largest study to date reported that chronic pain patients with a history of substance abuse evidenced higher rates of medication misuse compared to those without such history despite equivalent levels of prescribed opiates and similar self-ratings of medication effectiveness.…”
Section: Discussionsupporting
confidence: 92%
“…Research in non-HIV populations suggests that among individuals with chronic, nonmalignant pain, previous substance abuse is associated with an increased likelihood of opiate misuse (Schofferman 1993;Dunbar and Katz 1996;Michna et al 2004;Schieffer et al 2005). Although analogous investigations have not been conducted in HIV samples, it is likely that HIV patients with a problem drug use history would similarly evidence greater misuse of opiates than their non-problem-drug-using counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…Our main independent variables were five risk factors for opioid misuse derived from prior research: (1) age <45 at the time of the first opioid prescription, [14][15][16][17]19 (2) current or past drug use disorder, 14,15,17,20 (3) current or past alcohol use disorder, 14,21 (4) current or past tobacco use, 21,25 and (5) current or past mental health disorder (i.e., anxiety, depression, bipolar disorder, post-traumatic stress disorder, or schizophrenia). 15,[20][21][22] These conditions were identified from ICD-9-CM coded diagnoses from inpatient and outpatient visits (available online).…”
Section: Classification Of Risk Factors For Opioid Misusementioning
confidence: 99%
“…15,[20][21][22] These conditions were identified from ICD-9-CM coded diagnoses from inpatient and outpatient visits (available online). Drug and alcohol use disorders were defined by an ICD-9-CM code for abuse, dependence, poisoning, withdrawal, or psychosis within our study timeframe.…”
Section: Classification Of Risk Factors For Opioid Misusementioning
confidence: 99%
See 1 more Smart Citation